DEVELOPING READING WORKSHEET BASED ON TASKBASED LANGUAGE TEACHING TO TEACH STUDENTS’ READING COMPREHENSION FOR THE TENTH GRADE STUDENTS AT SMA NEGERI 3 MEDAN - Nurhanifa Lubis; Anni Holila Pulungan (Universitas Negeri Medan, 2021)
The objective of this study was to develop reading worksheet based on taskbased language teaching to teach students’ reading comprehension for tenth grade students at sma negeri 3 medan. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, materials development, validating by experts, revising, and final product. The subject of the study was the tenth-grade students in SMA Negeri 3 Medan. The data were gathered by reviewing documents, conducting an interview with the English teacher, and distributing the students' needs analysis questionnaires to X MIA 2 consists of 35 students to get the students’ needs. The interview and questionnaire results proved that the students needed reading worksheet based on task-based language teaching. The developed reading worksheets were validated by two experts which scored 3.77 and 3.87 on average. The scores approved that the reading worksheet based on task-based language teaching were very valid and suitable to use for the tenth-grade students in SMA Negeri 3 Medan. The result of the product was distributed to the students through bit.ly/TBLTworksheetKey words: Development, Reading, Worksheet, Task-Based Language Teaching.